Effect of Stimulated Salivary Volume on Dysbiosis of the Salivary Microbiome in Children and Young Adults - Tomoaki Shintani; Nami Obayashi; Tetsuya Yoshimoto; Toshinori Ando; Nagisa Morihara; Nanako Kataoka; Rie Miyata; Mai Yoshino; Hiroki Yoshii; Shin Morimoto; Yuka Hayashi; Masayuki Suzuki; et al. (International Dental Journal)
Objectives: This study aimed to determine the salivary factors that influence salivary bacterial counts and the microbiome composition in children and young adults. Methods: This cross-sectional study included 382 patients who visited the dental clinic in Hiroshima University Hospital. All participants underwent a saliva test and were divided into high- and low-bacterial-count groups based on the median bacterial count. Salivary factors and clinical variables, including the total number of teeth and plaque control record, were analyzed to determine their association with salivary bacterial counts. Furthermore, a comprehensive analysis of microbiome diversity and composition was performed using 16S rRNA sequencing. Results: Univariate and multivariate analyses identified stimulated saliva volume (SSV) and plaque control record as independent factors influencing salivary bacterial counts. Principal coordinate analysis revealed a significant decrease in beta diversity in the high-bacterial-count group. LEfSe analysis revealed Prevotella, Veillonella, Megafaella, Selenomonas, and TM7X as the 5 most abundant bacteria. The relative abundance of the 35 KEGG pathways exhibited significant differences. Furthermore, Prevotella and Veillonella were strongly associated with 25 functional pathways. Conclusion: Oral hygiene instruction is necessary even for children and young adults with relatively adequate SSV to maintain a healthy oral microbiome.